What's in a name? The valuation effect of directors’ sharing of surnames - Tan, Youchao; Xiao, Jason; (Colin) Zeng, Cheng; Zou, Hong (Journal of banking & finance, 2021)
Using surname sharing as a novel measure of social ties, we examine the effect of directors’ surname sharing on firm value. We find that boards with greater surname homogeneity are associated with lower firm value. This finding is not driven by familial ties. The negative effect of surname sharing on firm value is more pronounced when directors share rare surnames and when firms operate in regions with stronger clan systems, but is attenuated by stronger corporate governance mechanisms. The market reacts positively to plausibly exogenous director resignations that reduce director surname sharing, and negatively to board appointments that increase director surname sharing. Director surname sharing lowers firm value by reducing director dissension, granting excess executive compensation, and increasing related-party transactions. Overall, our results suggest that directors’ surname sharing, an easy-to-trace but previously neglected social tie, can have significant economic consequences.